2008
DOI: 10.1029/2008gc002048
|View full text |Cite
|
Sign up to set email alerts
|

A benchmark study on mantle convection in a 3‐D spherical shell using CitcomS

Abstract: [1] As high-performance computing facilities and sophisticated modeling software become available, modeling mantle convection in a three-dimensional (3-D) spherical shell geometry with realistic physical parameters and processes becomes increasingly feasible. However, there is still a lack of comprehensive benchmark studies for 3-D spherical mantle convection. Here we present benchmark and test calculations using a finite element code CitcomS for 3-D spherical convection. Two classes of model calculations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
265
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 293 publications
(299 citation statements)
references
References 85 publications
7
265
0
Order By: Relevance
“…Indeed, as can be seen in Fig. 14a, the changes in the vertical structures of incipient flows occur at around r η 10 4 (i.e., E 9.2), while, from earlier numerical studies [2,28,31], that the collapse of the SL-mode of convection occurs at the values of r η larger than 10 4 . It can, therefore, be conjectured that, for a range of 10 4 r η 10 4.5 , there exists an ST-mode of convection with convection cells of large horizontal length scales.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 77%
See 2 more Smart Citations
“…Indeed, as can be seen in Fig. 14a, the changes in the vertical structures of incipient flows occur at around r η 10 4 (i.e., E 9.2), while, from earlier numerical studies [2,28,31], that the collapse of the SL-mode of convection occurs at the values of r η larger than 10 4 . It can, therefore, be conjectured that, for a range of 10 4 r η 10 4.5 , there exists an ST-mode of convection with convection cells of large horizontal length scales.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 77%
“…14a, the classification of convective regimes, inferred from the changes in the horizontal length scales of convection cells, obtained by earlier numerical experiments of thermal convection in three-dimensional spherical shells [2,13,18,28,31]. Among the symbols in the figure, the triangles indicate the conditions for a so-called "sluggish-lid" (SL) mode of convection which is characterized by convection cells of large horizontal scales (see Fig.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The governing equations may be nondimensionalized as in the work of Zhong et al (2000) and Zhong et al (2008) via:…”
Section: Governing Equationsmentioning
confidence: 99%
“…However, Courtillot et al (2003) have collected various lines of evidence to support the existence of multiple possible sources of thermal plumes in the mantle. These include geochemical contrasts of 3 He/ 4 He and 21 Ne/ 22 Ne ratios between mid-ocean ridge basalts (MORBs) and ocean island basalts (OIBs), correlation of Large Igneous Provinces (LIPs) with impinging mantle plume heads, laboratory studies of thermal convection in viscous fluids [Whitehead and Luther, 1975;Jellinek and Manga, 2004], numerical convection studies [Steinberger and O'Connell, 1998;Zhong et al, 2000, Zhong et al, 2001McNamara and Zhong, 2004;Zhong et al, 2008], and seismic imaging of the deep mantle beneath Hawaii and Iceland [Wolfe et al, 1997]. Sleep (2006) has also investigated the origins of plumes using first principles and found that thermal boundary layers at the core-mantle boundary and 410-670 km transition zone result in thermal instabilities which generate thermal upwellings.…”
Section: Introductionmentioning
confidence: 99%